Rancang Bangun Sistem Informasi Rumah Makan Tersertifikasi Halal Mui Di Kota Bengkulu Berbasis Android - Karniawan, Roni; Sonita, Anisya (Jurnal Media Infotama, 2022)
The country of Indonesia is now experiencing a business development in the culinary field, so that local restaurants or restaurants compete to rack their brains to provide good and unique services to increase the interest of their respective customers. In increasing customers, in addition to providing good service, restaurants / restaurants must also look at the market share / sociology of the Muslim community, so that the halal label is very sensitive to people's decisions in choosing restaurants / restaurants. Halal certificate is a written fatwah of the Indonesian Ulema Council (MUI) which states the halalness of a product in accordance with Islamic law. Due to the high public interest in halal food and drinks, there are also many parties or individuals who try to take advantage of this condition by falsifying or deceiving consumers by falsifying other people's halal certificates to be included on their own food and beverage products. The application of technology that is currently developing can also be used for all areas of daily life, especially in the field of culinary tourism, especially in the use of mobile-based technology, namely Android, especially now that people are already aware of mobile-based technology and are very dependent on every daily activity. can help the public and tourists in the city of Bengkulu in looking for halal certified culinary without having to be confused in looking for references, menus and the nearest place to be able to enjoy halal culinary. This application for finding halal restaurants in Bengkulu city was built as a means of facilitating the community, especially for local people and tourists who want to visit Bengkulu and look for halal food. The halal culinary application that is implemented in the city of Bengkulu can help the public and tourists in finding halal food and provide map guidance when they want to go to the destination using a map integrated with Google Maps from the location of the application user to the destination.